A novel inverted ‘V’ flap in endo-DCR: case report - Munjal, Manish; Munjal, Shubham; Arora, Priyanka; Sharma, Salony; Arora, Vineeta; Kaur, Hardeep; Chawla, Deeksha; Sandhu, Loveleen; Kaur, Gursimran; ., Utkarash (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Endo-DCR has a successful outcome when the lacrimal sac is marsuplised on the nasal lateral nasal wall. The lacrimal sac and nasal mucosal edges heal by primary intention rather than by formation of granulation tissue with consequent restenosis or reclosure. An indigenous flap was utilized to cover the exposed bone following Endo-DCR in a young individual. The flap fashioned in an inverted ‘V’ prevented the granulation of secondary intent healing and thereby reclosure.